2022
DOI: 10.1039/d2ta01649d
|View full text |Cite
|
Sign up to set email alerts
|

Strain-free hybrid perovskite films based on a molecular buffer interface for efficient solar cells

Abstract: Strain is ubiquitous in perovskite based photovoltaic cells, but can be hardly well released in most perovskite films, which usually impose adverse effect on devices’ performance and lifetime. Here, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…To verify the strain in the lattice between pristine and 5% Zn, grazing incidence XRD was performed. 25,28,31 We selected grazing incidence angles of 0.5°, 2.5°, 5.0°, and 7.5°and showed the (100) planes of the control and Zn-5. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To verify the strain in the lattice between pristine and 5% Zn, grazing incidence XRD was performed. 25,28,31 We selected grazing incidence angles of 0.5°, 2.5°, 5.0°, and 7.5°and showed the (100) planes of the control and Zn-5. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the local lattice strain affecting the optoelectronic properties of perovskite lms has attracted attention. [24][25][26][27][28][29][30][31] Local lattice strain is caused by lattice distortion of the octahedron in a perovskite lm [24][25][26] or mismatched thermal expansion coefficients of perovskite and its substrates. 28,31 Saidaminov et al reported that the local lattice strain in a single cation/halide perovskite facilitates the formation of vacancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key driving forces for the differences in volume contraction are the coefficient of thermal expansion (CTE) a mismatch between perovskite film and ETL. 56 It is reported that the expansion coefficient of the PVK film is 6.1 Â 10 À5 K, which is larger than that of SnO 2 (4.0 Â 10 À6 K). 26 When PVK film cools down after thermal annealing, the contraction of the PVK film is limited by the underlying SnO 2 substrate, resulting in depth-dependent crystal lattice deformation within the PVK film.…”
Section: Effect Of Additive Mose 2 On the Pbi 2 And Pvk Filmsmentioning
confidence: 95%
“…Organic–inorganic hybrid perovskites have become promising optoelectronic materials due to their high carrier mobility, tunable direct band gap, low exciton binding energy, and long carrier diffusion length. The power conversion efficiency (PCE) of perovskite solar cells (PSC) has rapidly climbed from 3.8 to 25.7% in the past decade. The preparation methods of PSC mainly include spin-coating, ,, vapor deposition, and thermal evaporation . Among them, the spin-coating method is the most widely used, and it can be divided into a one-step solution method , and a sequential deposition method. In the sequential deposition method, perovskite films are obtained by the reaction of lead halide films (such as PbI 2 ) with organic halide solutions (such as formamidine iodide and methylammonium iodide). Compared with the one-step method, the sequential deposition method is reproducible and more easily forms vertically grown perovskite crystals .…”
Section: Introductionmentioning
confidence: 99%